Scientific Intuition – Balance of Art and Science in Homeopathy - Chauhan, Dinesh (Homœopathic Links, 2013)
The application of scientific intuition is effective in each and every area of life including homoeopathy, be it applied to the case witnessing process or the healing journey for the patient and the physician. The balance of science and intuition weaves into an effortless healing for the patient and the physician.
Keywords: Case taking; Case witnessing; Science; Scientific; Intuition; Case receiving (witnessing) process; Newton; Conscious effort; Effortless; Buddha; Three steps; Scientifically intuitive; Healing art; Dinesh Chauhan